Crystal structure of bis{2-[(E)-(4-fluorobenzyl)- iminomethyl]phenolato-k2 N,O}nickel(II) - Amalina Mohd Tajuddin; Amalina Mohd Tajuddin; Rohazila Mohammad Hanafiah; Nazlina Ibrahim; Hoong-Kun Fun; Suchada Chantrapromma (Acta Crystallographica Section E, 2024)
Non-Indexed Publication